2015
DOI: 10.3892/or.2015.3837
|View full text |Cite
|
Sign up to set email alerts
|

Association of annexin A2 with cancer development (Review)

Abstract: Annexin A2 (ANXA2) is a well-known calcium-dependent phospholipid binding protein widely distributed in the nucleus, cytoplasm and extracellular surface of various eukaryotic cells. It has been recognized as a pleiotropic protein affecting a wide range of molecular and cellular processes. Dysregulation and abnormal expression of ANXA2 are linked to a large number of prevalent diseases, including autoimmune and neurodegenerative disease, antiphospholipid syndrome, inflammation, diabetes mellitus and a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 144 publications
3
60
1
Order By: Relevance
“…Annexin A2 orchestrates multiple biological processes and clinical associations, particularly during cancer progression (16). It has been demonstrated that Annexin A2 dysregulation is associated with the onset, invasion, metastasis and drug resistance of cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 orchestrates multiple biological processes and clinical associations, particularly during cancer progression (16). It has been demonstrated that Annexin A2 dysregulation is associated with the onset, invasion, metastasis and drug resistance of cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we used the combination of co-IP and MS to identify 6 molecular partners of UBAP2, including Annexin A2. Accumulating evidence have showed that Annexin A2 is aberrantly expressed in a wide spectrum of cancers, including HCC [15-17]. Annexin A2 involved in several pathological processes, such as tumor cell adhesion, proliferation, apoptosis, tumor neoangiogenesis, invasion and metastasis [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 is overexpressed in numerous tumours, including glioma . Aberrantly, expression of ANXA2 plays important roles in tumour development by regulating cell proliferation, apoptosis, invasion and metastasis …”
Section: Introductionmentioning
confidence: 99%